Church of spies : the Pope's secret war against Hitler - Riebling, Mark (New York : Basic Books, 2015)
History has accused wartime pontiff Pius the Twelfth of complicity in the Holocaust and dubbed him "Hitler's Pope." Riebling shows that, in reality, Pius ran the world's largest church, smallest state, and oldest spy service. Skimming from church charities to pay covert couriers, and surreptitiously tape-recording meetings with top Nazis, Pius played sent birthday cards to Hitler-- while secretly plotting to kill him. Fearing that overt protest would impede his covert actions, he muted his public response to Nazi crimes.
Darkness over the earth -- The end of Germany -- Joey Ox -- Tyrannicide -- Someone to kill him -- Luck of the devil -- The black chapel -- Absolute secrecy -- The X-report -- Warnings to the West -- The brown birds -- Forging the iron -- Conversations in the crypt -- Shootout in the cathedral -- Two bottles of cognac -- The Siegfried blueprints -- The white knight -- Prisoner of the Vatican -- It must happen -- Holy Germany -- The trove -- Hell -- The gallows -- A dead man -- The Emerald Lake.
Includes bibliographical references (pages 331-357) and index.
Keywords: Pius -- XII, -- Pope, -- 1876-1958.; Catholic Church -- Foreign relations -- Germany; Germany -- Foreign relations -- Catholic Church; World War, 1939-1945 -- Vatican City; World War, 1939-1945 -- Religious aspects -- Catholic Church; Anti-Nazi movement -- Vatican City